2008
DOI: 10.1007/s10803-008-0648-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eating Attitudes between Adolescent Girls with and without Asperger Syndrome: Daughters’ and Mothers’ Reports

Abstract: Despite the evidence that individuals with Asperger syndrome (AS) have a propensity for being underweight or having comorbid eating disorders, no previous research has compared the eating attitudes of adolescent girls with AS to typically developing peers. This study compared reports of eating problems provided by the adolescent girls themselves (56 with and 56 without AS) and their mothers on the EAT-26. Results indicated that adolescent girls with AS are at a higher risk for eating problems than their typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
(56 reference statements)
1
21
0
1
Order By: Relevance
“…The everyday management of mealtime behaviors among children with ASD can have a negative impact on family routines, become a significant stressor for families, and be a challenge for clinicians (Cornish, 1998;Williams et al, 2000). Previous studies on the prevalence of food selectivity in individuals with ASD have reported highly variable rates, ranging from 13% to 87%, probably accounted by the use of different methodologies and distinct definitions of food selectivity (Ahearn et al, 2001;Bandini et al, 2010;Collins et al, 2003;Cornish, 1998;Dominick et al, 2007;Field et al, 2003;Kalyva, 2009;Klein & Nowak, 1999;Nadon et al, 2011;Schmitt et al, 2008;Schreck & Williams, 2006;Schreck et al, 2004;Suarez et al, 2013;Whiteley et al, 2000;Williams et al, 2000Williams et al, , 2005. In our study we found similar levels of food refusal to the incidence rates of this domain reported by other authors Schreck et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The everyday management of mealtime behaviors among children with ASD can have a negative impact on family routines, become a significant stressor for families, and be a challenge for clinicians (Cornish, 1998;Williams et al, 2000). Previous studies on the prevalence of food selectivity in individuals with ASD have reported highly variable rates, ranging from 13% to 87%, probably accounted by the use of different methodologies and distinct definitions of food selectivity (Ahearn et al, 2001;Bandini et al, 2010;Collins et al, 2003;Cornish, 1998;Dominick et al, 2007;Field et al, 2003;Kalyva, 2009;Klein & Nowak, 1999;Nadon et al, 2011;Schmitt et al, 2008;Schreck & Williams, 2006;Schreck et al, 2004;Suarez et al, 2013;Whiteley et al, 2000;Williams et al, 2000Williams et al, , 2005. In our study we found similar levels of food refusal to the incidence rates of this domain reported by other authors Schreck et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, food selectivity is often associated with inadequate nutrient intake (i.e., estimated average requirement [EAR], and adequate intake [AI]) suggesting that a limited diet may put any child at risk for nutritional deficiency Bicer & Alsaffar, 2013;Schmitt et al, 2008). However, studies examining the prevalence of food selectivity in children with ASD have reported highly variable rates, ranging from 13% to 87% (Ahearn et al, 2001;Bandini et al, 2010;Collins et al, 2003;Cornish, 1998;Dominick et al, 2007;Field, Garland, & Williams, 2003;Kalyva, 2009;Klein & Nowak, 1999;Nadon et al, 2011;Schmitt et al, 2008;Schreck & Williams, 2006;Schreck et al, 2004;Suarez, Nelson, & Curtis, 2013;Whiteley, Rodgers, & Shattock, 2000;Williams et al, 2000Williams et al, , 2005. For instance, Whiteley et al (2000) reported that 83% of parents indicated that their children ate a restrictive repertoire of foods.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that these two conditions can be comorbid [29] is at least in line with this view, although comorbidity alone does not help us understand why they are associated. The fact that many children with autism are ‘picky eaters’ and resist eating new foods [37] provides another impetus for investigating the link between anorexia and autism further, as does the finding that girls with AS score significantly higher than controls on the Eating Attitudes Test (EAT)-26 [38], a screening instrument for eating disorders [39]. …”
Section: Introductionmentioning
confidence: 99%
“…Adolescent girls with Asperger syndrome have more eating problems than their typically developing peers (Kalyva 2009). In those with severe and enduring eating disorders an unrecognised ASD may impede and complicate treatment, and worsen prognosis (Wentz 2005).…”
Section: Eating Disordersmentioning
confidence: 99%